THE POSSIBILITY OF USAGE OF METABOLIC CORRECTION THERAPY IN PATIENTS WITH ISCHEMIC HEART DISEASE AND HEART FAILURE - I. V. Sergienko (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2015)
Aim. To estimate an effect of metabolic corrector mildronate on cardiac hemodynamics and endothelium function in patients with ischemic heart disease (IHD) and heart failure (HF)Material and methods. 60 patients with IHD and HF of I-III functional class according to NYHA were included into the study. 30 patients of the main group received mildronate at a daily dose of 1000 mg during 3 months additionally to standard therapy. Patients of the control group took standard therapy only. Cardiac function was estimated by 4D Gated Equilibrium Radionuclide Ventriculography. The endothelium function was measured as endothelium dependent vasodilation.Results. During 3 months mildronate therapy resulted in increase of left ventricular (LV) ejection fraction, peak filling and peak ejecting rate of LV.Conclusion. Metabolic corrector mildronate has positive effect on cardiac function in patients with IHD and CHF.